Protease-Activated Receptor Type 1 Activation Enhances Osteogenic Activity in Human Periodontal Ligament Stem Cells - Emanuel Silva Rovai; Lucas Macedo Batitucci Ambrósio; Bruno Nunes de França; Letícia Rodrigues de Oliveira; Letícia Miquelitto Gasparoni; Carla Renata Sipert; Marinella Holzhausen (Stem Cells International)
Protease-activated receptor 1 (PAR1) has been associated to tissue repair and bone healing. The aim of the present study was to evaluate the effect of PAR1 activation on the osteogenic activity of human periodontal ligament stem cells (PDLSCs). PDLSCs were cultured in the presence of PAR1-selective agonist peptide (100 nM), thrombin (0.1 U/mL), or PAR1 antagonist peptide (100 nM). Calcium deposits, calcium concentration (supernatant), alkaline phosphatase activity (ALP), cell proliferation, and gene (qPCR) and protein expression (ELISA assay) of osteogenic factors were assessed at 2, 7, and 14 days. PAR1 activation led to increased calcium deposits (p<0.05), calcium concentration (p<0.05), ALP activity (p<0.05), and cell proliferation (p<0.05). Further, PAR1 activation may increase gene and protein expression of Runx2 (p<0.05) and OPG (p<0.05). In conclusion, PAR1 activation increases osteogenic activity of PDLSCs, providing a possible new strategy for periodontal regenerative therapies.